2008
DOI: 10.1123/jtpe.27.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Choice on Student Motivation and Physical Activity Behavior in Physical Education

Abstract: This study examined the effects of increased autonomy on (a) self-determination and (b) physical activity levels. Seventh- and eighth-grade girls (N = 122) in four classes participated in two fitness units (one allowing choice of activities, the other no-choice). The order of the units was counterbalanced, so that two classes participated in the choice unit first, and the other two participated in the no-choice unit first. The abridged Situational Intrinsic Motivation Scale (SIMS) was administered after each u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 40 publications
7
57
0
5
Order By: Relevance
“…As previously reported (Ward, Wilkinson, Graser & Prusak, 2008), this study confirms the need for research to determine the influence of gender differences in relation to choice in PE, as well as the various motivational determinants of PA in PE. Future research might also focus on expanding the sample size of the current study to include more schools over a wider geographic and demographic area.…”
Section: Future Directionssupporting
confidence: 66%
“…As previously reported (Ward, Wilkinson, Graser & Prusak, 2008), this study confirms the need for research to determine the influence of gender differences in relation to choice in PE, as well as the various motivational determinants of PA in PE. Future research might also focus on expanding the sample size of the current study to include more schools over a wider geographic and demographic area.…”
Section: Future Directionssupporting
confidence: 66%
“…For example, explaining the relevance of activities and providing opportunities for students to make choices during lessons are considered important strategies to promote autonomous student motivation and increase MVPA (Cheon et al, 2012;Perlman, 2013). But, evidence regarding the specific effects of providing choice on motivation towards PE and MVPA during PE lessons is limited (Lonsdale et al, 2009;Ward et al, 2008) and no study has examined the effects of explaining relevance on these outcomes. Little experimental evidence from other domains exists, but correlational analyses suggest that relevance may be more important than choice in terms of students' motivation towards academic subjects (Assor et al, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent SDT-based interventions have successfully enhanced student motivation towards PE (Chatzisarantis and Hagger, 2008;Cheon et al, 2012;Perlman, 2013;Ward et al, 2008); however, there is less evidence that SDT-based interventions in PE can influence actual MVPA behavior. In particular, there is a dearth of evidence gathered using objective MVPA measures (e.g., accelerometers) (Perlman, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, teachers engaged in an autonomy-supportive intervention are more likely to adopt and implement a highly autonomy-supportive learning context (Perlman, 2011b;Perlman & Piletic, 2012;Tessier et al 2010). In addition, students engaged in a highly autonomy-supportive setting indicated higher levels of enjoyment (Mandigo et al, 2008) and demonstrated more self-regulated behavior (Ward et al, 2008).…”
Section: Social Context and Physical Educationmentioning
confidence: 99%
“…Within physical education, research on self-determined social contexts has been focused on: (a) interventions to change teacher's abilities to implement a motivationally-supportive context (Chatzisarantis & Hagger, 2009;Perlman, 2011b;Perlman & Piletic, 2012;Prusak, Treasure, Darst, & Pangrazi, 2004;Tessier, Sarrazin, & Ntoumanis, 2010) and (b) the applied benefits of engaging students in diverse social contexts (Mandigo, Holt, Anderson, & Sheppard, 2008;Mouratidis, Vansteenkiste, Lens, & Sideridis, 2008;Murcia, Lacarcel, & Alvarez, 2010;Ward, Wilkinson, Graser, & Prusak, 2008). A summary of findings from the aforementioned studies indicate that teachers can be taught to use instructional behaviors that are more autonomy-supportive and that students benefit (e.g., enhanced motivation) from being involved in a highly-autonomy-supportive setting.…”
Section: Social Context and Physical Educationmentioning
confidence: 99%